Qualitative Analysis of the Influence of Hadith Methodology on the Development of Ibn Haitsam's Scientific Methodology - Bryan Pandu Permana; Miftakhussurur; AA Hubur (Siber International Journal of Sport Education, 2024)
This research reveals the influence of hadith methodology on the development of scientific methodology pioneered by Ibn Haitsam. The study aims to reveal the relationship between these two methodologies by analyzing through comparative studies, biographical studies and the works of Ibn Haitsam which are then analyzed qualitatively. This study reveals a fairly strong relationship between the Hadith methodology in verifying and checking the truth of the sanad with the scientific methodology of Ibn Haitsam. This study contributes to a deeper understanding of the relationship between the influence of Islamic science and the development of scientific methodology of science.